Effect of Multi-walled Carbon Nanotube on Mechanical Properties of Kenaf/Polypropylene Composites / Zakaria Razak...[et al.] - Razak, Zakaria; Sulong, Abu Bakar; Muhamad, Norhamidi; Md Radzi, Mohd. Khairol Fadzly; Tholibon, Dulina; Tharazi, Izdihar; Ismail, Nur Farhani (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Kenaf fibre has a high potential to be used for composite reinforcement in hybrid composites. It has been varying combinations of physical and mechanical properties, such as low cost, low density, high strength and stiffness. Carbon nanotubes (CNTs) are encouraging additives for polymer composites due to their excellent special mechanical, electrical, and thermal properties. The compounded samples were organized into test specimens by injection moulding machine. The composites contained 1, 2, 3 and 4 wt% multi-walled carbon nanotubes (MWCNT). The purpose of this study is to investigate the mechanical properties of kenaf core fibre with a weight fraction of 30 wt% and varying weight fraction of MWCNT. The injection moulding technique is used to prepare the composite specimens for tensile, flexural and impact tests in accordance to the ASTM D638, ASTM D790 and ASTM D256 respectively. The optimum properties have been observed at MWCNT 3 wt% with the impact strength of, 8.512Kj/m2, tensile strength, 23.447 MPa, Young's modulus, 1865.950 MPa, flexural strength, 36.728MPa and a flexural modulus, 1826.121 MPa.